An integrated approach based on anp, dematel and electre methodologies for personnel selection and an application in industry - Demirci, Ayşe Ecenaz (My University, 2018)
ÖZETPERSONEL SEÇİMİNDE ANALİTİK AĞ SÜRECİ, DEMATEL VE ELECTRE YÖNTEMLERİNE DAYALI BÜTÜNLEŞİK BİR YAKLAŞIM VE ENDÜSTRİDE BİR UYGULAMAOrganizasyon hedeflerinde kaliteli işgücü önemli bir değer olduğundan personel seçimi şirketler için önemli bir konudur. Personel seçimi, en uygun personeli seçerek organizasyon taleplerine ulaşmayı amaçlayan ve işe alımdan sorumlu olan ‘İnsan Kaynakları’ disiplininin alt koludur. Personel seçimi, belirli bir meslek pozisyonu için çoklu kriterler bulunması sebebiyle ‘Çok Kriterli Karar Verme’ problemi olarak düşünülür. Personel seçimi problemlerinin yapısında hem niteliksel hem niceliksel kriterler bulunur. Bu nedenle, ‘Çok Kriterli Karar Verme’ yöntemleri, personel seçimi problemlerinin çok kriterli yapısıyla başa çıkabilmek için en iyi yöntemlerden biridir. Bu tez çalışmasında, öncelikle DEMATEL yöntemi kulanılarak, bir şirketin mühendislik pozisyonu kriterlerinin ağ ilişki haritası belirlenmiştir. İkinci olarak, bu ağ ilişki haritası Analitik Ağ Süreci yöntemine veri olarak kullanılmıştır. Analitik Ağ Süreci yöntemini uygulamak için, Superdecisions Yazılımı kullanılmış ve kriterlerin ikili karşılaştırmaları uzman görüşlerine dayalı olarak yapılmıştır. Yedi kriterin ağırlıkları, Analitik Ağ Süreci metodu yoluyla elde edilmiştir. Son olarak, adayları sıralamak için ELECTRE yöntemi kullanılmıştır. Bununla birlikte, uygulamanın her aşamasında (DEMATEL, Analitik Ağ Süreci ve ELECTRE), uzman görüşü kullanılmıştır. Bu tez çalışması, hem teorik açıdan yeni bir yöntem önermeye ilişkin, hem de bunu bir endüstride uygulamaya ilişkin olarak önemli bir yapı sağlamaktadır. Diğer çalışmalardan farklı olarak, ‘Çok Kriterli Karar Verme’ yöntemleri olan DEMATEL, Analitik Ağ Süreci ve ELECTRE birlikte uygulanmıştır.

TABLE OF CONTENTSACCEPTENCE AND APPROVAL DOCUMENTiiACKNOWLEDGEMENTiiiÖZETvABSTRACTviSYMBOLS AND ABBREVIATIONSviiLIST OF TABLESixLIST OF FIGURESxi1.INTRODUCTION12.PERSONNEL SELECTION32.1. The Historical Background of Human Resources Management and Personnel Selection32.2. Functions of Personnel Selection52.2.1. Personnel selection process52.3 Importance of Personnel Selection 112.4 Personnel Selection Policies112.4.1. Measurability of ability level112.4.2. Measurability of job specifications112.5 Trends in Personnel Selection123. LITERATURE REVIEW133.1. Criteria 203.1.1. Analysis of general criteria including both white and blue collars203.2. Methods233.2.1.Method analysis in general23 3.2.1.1. Single method analysis in general24 3.2.1.2. Hybrid method analysis in general25 3.2.1.3. General method analysis..29 3.2.1.4. Method classification in terms of job positions..313.2.2. Sector analysis of methods49 3.2.2.1.The frequency of AHP technique with respect to sectors51 3.2.2.2.The frequency of fuzzy set theory technique with respect to sectors53 3.2.2.3.The frequency of fuzzy TOPSIS technique with respect to sectors55 3.2.2.4.The frequency of fuzzy AHP technique with respect to sectors56 3.2.2.5.The frequency of TOPSIS technique with respect to sectors584.METHODS634.1. Proposed Methodology634.2. Proposed Techniques in Proposed Methodology654.2.1. Analytic hierarchy process65 4.2.1.1.The advantages of AHP70 4.2.2. Analytic network process71 4.2.2.1. History and attributes of ANP71 4.2.2.2. Comparison between AHP and ANP72 4.2.2.3. Network structure, feedback and dependency in ANP73 4.2.2.4. ANP steps754.2.3. DEMATEL78 4.2.3.1. Brief history and function of DEMATEL78 4.2.3.2. Application fields of DEMATEL79 4.2.3.3. DEMATEL steps794.2.4. ELECTRE83 4.2.4.1. Advantages of ELECTRE.85 4.2.4.2. ELECTRE Steps.855.THE APPLICATION OF THE PROPOSED METHODOLOGY91 5.1. DEMATEL Part91 5.2. ANP Part97 5.3. ELECTRE Part1006.CONCLUSION 109APPENDIX A: PERSONNEL SELECTION LITERATURE REVIEW TABLE.......................... 110APPENDIX B: GENERAL CRITERIA TABLE......................................................................... .... 125REFERENCES133RESUME145 ABSTRACTAN INTEGRATED APPROACH BASED ON ANP,DEMATEL AND ELECTRE METHODOLOGIES FOR PERSONNEL SELECTION AND AN APPLICATION IN INDUSTRYPersonnel selection is an important issue for the companies since skilled labor is a critical asset in organization goals. Personnel selection is sub branch of human resources discipline that deals with recruitment so as to meet the organization’s demand by selecting the most matching personnel. Personnel selection is considered as a ‘Multi Criteria Decision Making’ problem since multi criteria for a specific job position exist. The framework of the personnel selection problem includes both qualitative and quantitative criteria. Therefore, multi criteria decision making techniques is one of the best methods to cope with the multi criteria structure of the personnel selection problems.In this thesis, firstly the Network Relationship Map of the criteria for a company’s engineering position is determined via DEMATEL method. Secondly, Network Relationship Map is used as data for Analytic Network Process method. Superdecisions Software is utilized to implement Analytic Network Process method and pairwise comparisons of criteria are performed based on experts’ views. Weights of the seven criteria are obtained by Analytic Network Process method. Finally, ELECTRE method is applied to rank the candidates. However, expert opinion is used in every stage of the methodology (DEMATEL, Analytic Network Process and ELECTRE). This thesis provides important framework in terms of both theoretically by proposing a new tool and practically by providing an implementation in industry. Different from the existing studies, multi criteria decision making methods Analytic Network Process, DEMATEL and ELECTRE are implemented together.
Keywords: Çok amaçlı karar verme; Çok kriterli karar verme; Decision making; Endüstri mühendisliği; Endüstriyel yönetim; Industrial engineering; Industrial management; Karar verme; Multiple criteria decision making; personel seçimi Multiple criteria decision making; personnel selection; Production management; Üretim yönetimi